Internal audit reports post Sarbanes-Oxley : a guide to process-driven reporting - Switzer, Susan, 1945- (John Wiley & Sons, 2007)
Brimming with commonsense advice delivered in a conversational, easy-to-read style, Internal Audit Reports Post Sarbanes-Oxley: A Guide to Process-Driven Reporting helps you transform raw data into useable information and then translate that information into actionable messages while complying with the SOX Act.